2016
DOI: 10.1159/000452425
|View full text |Cite
|
Sign up to set email alerts
|

Development of Photoonycholysis with Vandetanib Therapy

Abstract: Vandetanib therapy is a novel once-daily oral multitargeted tyrosine kinase inhibitor, which is currently used in advanced or metastatic medullary thyroid cancer. Skin toxicities are among the most prevalent adverse events reported with this targeted therapy (e.g. acne-like rash, hand-foot skin reaction, hair changes, and paronychia). In addition, photosensitivity reactions may affect more than one third of treated patients. We report here 2 patients developing photosensitivity reactions with vandetanib therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…A previous study reported that vandetanib resulted in dermatologic side effects in 37% of the patients, causing sunburn-like erythema in the sun-exposed areas in most of the patients [3]. On the other hand, it has also been reported that vandetanib may lead to a sense of burning, edema, and bulla formation within several days or weeks after the initiation of the therapy [1].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study reported that vandetanib resulted in dermatologic side effects in 37% of the patients, causing sunburn-like erythema in the sun-exposed areas in most of the patients [3]. On the other hand, it has also been reported that vandetanib may lead to a sense of burning, edema, and bulla formation within several days or weeks after the initiation of the therapy [1].…”
Section: Discussionmentioning
confidence: 99%
“…As the EGFRs are intensely expressed in the epidermis, the hair follicles and the sebaceous glands, these inhibitors mostly lead to dermatological side effects in 50%-100% of the cases [5]. Most common dermatological side effects induced by vandetanib include papulopustular eruption, hand-foot syndrome, hyperpigmentation, mucosal changes, dry skin, hair changes, paronychia, and pyogenic granuloma [1,2,5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations